PENDAMPINGAN PEMBELAJARAN BAHASA INGGRIS MELALUI METODE GAMES - Kara, Yuliana Maria D’ Karmel; Ningsih, Ningsih; Separ, Fransiskus Maria; Ambat, Fibrianto; Yoma, Kresensiana; Endung, Yasinta Par; Djou, Ana Maria Gadi (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims at increasing English learning motivation through games. English learning methods used in Rumah Baca Sukacita are the Simon Says Game, Taboo Game and Four in Row Game. This activity is held at Rumah Baca Sukacita Ende and consists of three groups; the group early childhood education and Kindergarten, the Group Elementary School and the group Junior High School. This activity had three stages namely preparation, implementation and evaluation. The result of this activity showed positive activity. Result of this activity shows that the learning process using games can increase motivation in English vocabulary, self-confidence, and participation in learning English.